2007
DOI: 10.1093/ajcn/86.5.1347
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite polymorphism in the heme oxygenase-1 gene promoter is associated with iron status in persons with type 2 diabetes mellitus

Abstract: Type 2 diabetes patients carrying short (GT)(n) repeats may have higher ferritin values and greater HO enzymatic activity and may have greater susceptibility to diabetes than may those with long (GT)(n) repeats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
7
19
0
Order By: Relevance
“…They showed elevated serum ferritin and TBI (Arredondo et al 2007). In this study, we found similar behavior in both T2D parents and their offspring, with elevated serum ferritin, TBI and low transferrin receptor.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…They showed elevated serum ferritin and TBI (Arredondo et al 2007). In this study, we found similar behavior in both T2D parents and their offspring, with elevated serum ferritin, TBI and low transferrin receptor.…”
Section: Discussionsupporting
confidence: 77%
“…Bilirubin concentrations were measured at 530 nm (Shimadzu, model UV-1601). HO activity was expressed as nmole of bilirubin/mg protein/h (bilirubin molar extinction coefficient: e = 43.5 mM -1 9 cm -1 ) (Arredondo et al 2007). …”
Section: Heme Oxygenase Activitymentioning
confidence: 99%
“…As described earlier, 33 the distribution of the numbers of (GT) n showed a bimodal pattern with two main peaks at 21 GT repeats (15.2% for inhibitor-positive patients and 14.3% for inhibitor-negative patients) and 29 GT repeats (24.7% for inhibitor-positive patients and 24.5% for inhibitor-negative patients). Based on the frequency distribution in our cohort of patients, and as described in previous reports, [33][34][35] we divided the alleles into three subclasses: class S (<21 repeats); class M (21-29 repeats) and class L (≥30 repeats) alleles. The c 2 test for independence between allelic classes confirmed the Hardy-Weinberg equilibrium in both the inhibitor-negative and inhibitor-positive groups.…”
Section: Allele Frequencies At the Polymorphic Locussupporting
confidence: 71%
“…Free radical formation may play a role in the pathogenesis of diabetes by disrupting insulin action and total body glucose disposal. The iron act as a powerful prooxidant and the oxidative stress is increased in glucose-intolerant states [27][28][29]. The presence of poor glycemic control, hyperglycemia, iron overload, and protein glycation will all lead to oxidative stress causing the early appearance of microvascular complications (retinopathy and nephropathy) [8,24,30].…”
Section: Discussionmentioning
confidence: 99%